2016
DOI: 10.5897/err2016.2756
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of the effects of physical education lessons planned in accordance with cooperative learning approach on secondary school students problem solving skills

Abstract: The purpose of the present research was to investigate the effects of physical education lessons planned in accordance with cooperative learning approach on secondary school students' problem solving skills. The research was conducted on 48 students studying at Konya/Selçuklu Şehit Mustafa Çuhadar Secondary School in fall semester of 2015-2016 school year. The research utilized an experiment (24 students) and a control (24 students) group. In order to investigate the effects of physical education lessons plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Both systematic reviews reported effects on the cognitive, physical, social, or affective domains linked to learning. Thus, the positive outcomes of CL implementation have been verified in social/motor skills [18,19], social skills [20][21][22], motor/physical skills [23,24], cognitive skills [25,26] and affective learning [27].…”
Section: Introductionmentioning
confidence: 95%
“…Both systematic reviews reported effects on the cognitive, physical, social, or affective domains linked to learning. Thus, the positive outcomes of CL implementation have been verified in social/motor skills [18,19], social skills [20][21][22], motor/physical skills [23,24], cognitive skills [25,26] and affective learning [27].…”
Section: Introductionmentioning
confidence: 95%
“…Students developed the ability to use their decision-making skills to solve various problems in the game context (Dyson, 2001). With reference to cooperative games, students who participated in cooperative group PE lessons were happy to help their peers, which significantly improved their problem-solving skills (Gorucu, 2016). PE and sports training has a positive effect on high school students' problem-solving skills (Sozen, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary for children to have problemsolving skills. The benefit of updating problem-solving skills is very important for every part of students' forthcoming life, both personal and social life (Gorucu, 2016). Children with well-developed problem-solving skills will be able to identify effective solutions to problem (Thompson, Bhatt, & Watson, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes PE teachers confuse the implementation of CL with the implementation of specific activities and games, which causes problems for the class to act truly as a group . Another of the main problems of teachers in the application of the CL is found in the difficulties that students have in solving their problems, so it is necessary to establish longitudinal programs of intervention (Gorucu, 2016). On some occasions, in the teacher's eagerness to apply the CL in the classroom, they forget what the didactic purposes of the proposed interventions are (Wallhead and Dyson, 2017).…”
Section: Introductionmentioning
confidence: 99%